2020
DOI: 10.1017/s1092852920001431
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor among patients with alcoholism

Abstract: Abstract Background: Brain-derived neurotrophic factor (BDNF) is involved in neurogenesis and in the protection against oxidative damage and neuronal apoptosis. After exercise, there is an increased expression of this myokine, especially in skeletal muscle and brain. Low BDNF levels have been described in neurodegenerative diseases. Alcoholics show both muscle atrophy and brain atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…However, one of the most recent studies showed that chronic alcoholism was not associated with changes in central BDNF, i.e. brain atrophy, but rather a measure of BDNF expressed in peripheral tissue 94 . Therefore, the inverse association between BDNF and alcohol consumption previously noticed could be due to other underlying factors, such as depression 95 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, one of the most recent studies showed that chronic alcoholism was not associated with changes in central BDNF, i.e. brain atrophy, but rather a measure of BDNF expressed in peripheral tissue 94 . Therefore, the inverse association between BDNF and alcohol consumption previously noticed could be due to other underlying factors, such as depression 95 .…”
Section: Discussionmentioning
confidence: 95%
“…brain atrophy, but rather a measure of BDNF expressed in peripheral tissue. 94 Therefore, the inverse association between BDNF and alcohol consumption previously noticed could be due to other underlying factors, such as depression. 95 Dietary patterns and foods could also contribute to the observed differences.…”
Section: Discussionmentioning
confidence: 98%
“…The term S100B refers to a protein identified in the mid-1960s from brain extracts that is characterized by solubility in a 100% saturated solution with ammonium sulfate [ 98 ]. S100B is used as a biomarker of brain damage [ 99 , 100 ], mechanical brain injury, traumatic brain injury induced by alcoholic intoxication, and long-term chemical external impacts (prolonged consumption of ethanol or other psychoactive addictive substances), as well as complex biochemical degenerative processes (associated with Parkinson and Alzheimer’s diseases) [ 101 ]. Khandare et al revealed a correlation of S100B levels (along with neuron-specific enolase protein) with the severity of the infract in ischemic stroke, pointing to S100B as a predictive marker protein for the assessment of how strong the ischemic strike is and what clinical prognosis may be expected.…”
Section: Resultsmentioning
confidence: 99%